2004
DOI: 10.1242/jeb.00839
|View full text |Cite
|
Sign up to set email alerts
|

Sodium and potassium currents of larval zebrafish muscle fibres

Abstract: .p.f.) are described. In inner muscle, the outward currents were half-activated at -1.0·mV and half-inactivated at -30.4·mV, and completely inactivated within 100·ms of depolarization. The inward currents of inner fibres were half-activated at -7.3·mV and half-inactivated at -74.5·mV and completely inactivated within 5·ms of depolarization. Inner muscle fibres were found to support action potentials, while no action potentials could be evoked in outer muscles. In inner muscle fibres, all tested levels of depol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
62
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(63 citation statements)
references
References 43 publications
1
62
0
Order By: Relevance
“…In fish, the slow (red, tonic) muscle fibers are responsible for slow sustained swimming, whereas the fast fibers are for heavy bending during fast swimming or escapes. Graded control of the motion is achieved through regulation of the number and types of the fibers activated (1-3), and in fish, moreover, the slow fibers can make graded contractions by themselves (35,37). The slow muscle fibers in zebrafish larvae lack Na V -dependent APs and Table S2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fish, the slow (red, tonic) muscle fibers are responsible for slow sustained swimming, whereas the fast fibers are for heavy bending during fast swimming or escapes. Graded control of the motion is achieved through regulation of the number and types of the fibers activated (1-3), and in fish, moreover, the slow fibers can make graded contractions by themselves (35,37). The slow muscle fibers in zebrafish larvae lack Na V -dependent APs and Table S2.…”
Section: Discussionmentioning
confidence: 99%
“…are tightly coupled across myotomes to distribute the synaptic signal to neighboring cells for averaging of the depolarization drive, as well as for priming the activation of the next segment (35,37). Such a signaling process may also work in the Ciona muscle band, whereas it remains unclear how these tonic fibers of vertebrates load Ca 2+ to make graded responses.…”
Section: Discussionmentioning
confidence: 99%
“…where V 50,act , V 50,inact , s a and s i are the values for V 50 (voltage of half activation) and slope of activation/inactivation, respectively, taken from Buckingham and Ali (2004). The values for m τ and h τ were taken as the time constants of activation or inactivation, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Immature retinal ganglion neurons (RGN) exhibit single-spike firing during postnatal days P1 to P11, thought to be a consequence of insufficient calcium-activated potassium current [I K(Ca) ], while retinal amacrine cells fire single spikes because of insufficient Na + conductance and a lack of removal of Na + inactivation (Eliasof et al, 1987). In a recent paper in which we described the steady-state and kinetic properties of a sodium and potassium current present in the inner muscles of the zebrafish (Buckingham and Ali, 2004), we suggested that once-only firing may arise from the fact that the sodium current is rapidly inactivated and requires a rebound to more hyperpolarized voltages before sufficient channels are reactivated. Since at a resting potential of approximately -70·mV in the larvae (Buss and Drapeau, 2000) and approximately -80·mV in the adult (Westerfield et al, 1986) up to 70% of sodium current is inactivated (Buckingham and Ali, 2004), a second spike might only be possible after a hyperpolarization.…”
mentioning
confidence: 99%
See 1 more Smart Citation